Directive Speech Act Analysis In “Inside Out 2” Movie Utterances - Amanda Dwi Juliatining Arum (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
This study aimed to analyze the use of directive speech acts in the film “Inside Out 2”, focusing on how commands, orders, requests, and suggestions shape the dynamics of conversation. This study examined how language functions to influence and guide behavior in everyday movies. The data source was the dialogue spoken in the movie with 10 main emotional characters used 10 main emotional characters because they are figures in the brain that influence to do something, and this study used a qualitative descriptive design to systematically identify directive speech acts. Data were collected through observation methods with non-participatory techniques, and analyzed using the pragmatic identity method with contextual analysis technique. The results showed that commands, with 43 examples, were the most common directive speech acts, indicating a preference for politeness. Requests followed with 30 instances, and suggestions appeared 8 times, indicating subtle influence, while asks was the least frequent with 5 instances, highlighting the sparing use of direct authority, and instructions were found in 14 utterances. These findings underscore how understanding directive speech acts contributes to the flow of interaction and dynamics in the movie context.